ANALISIS BIAYA DIFERENSIAL DALAM MENGAMBIL KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS DI PT. AFIFARMA KEDIRI TAHUN 2022 - Wardani, Finka Agustin; Zaman, Badrus; Solikah, Mar’atus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the differential cost calculation for a special order product of paracetamol syrup 60 ml at PT. Afi Farma Kediri. The approach used in this study is a quantitative approach using data in the form of numbers and analyzed with differential cost information. Conclusion (1) Calculation of differential costs and differential income of PT. Afi Farma for the paracetamol syrup 60 ml product, namely the company earned a profit of IDR 33.,117.592. This profit comes from differential income on product sales with a total of IDR 929.500.000 and differential costs incurred for production namely IDR 591.382.408. (2) Based on the analysis of differential income and cost calculations, that the decision of PT. Afi Farma's acceptance of a special order for paracetamol syrup 60 ml was the right decision. This decision succeeded in making a positive contribution to the profits of the company as a whole.